How Risky is Investment in Human Capital? - Joop Hartog; Hans van Ophem; Simona Maria Bajdechi (Tinbergen Institute, 2004)
The risk of investment in schooling has largely been ignored. We assess thevariance in the rate of return by surveying the international empirical literature from this freshperspective and by simulating risky earnings profiles in alternative options. choosingparameters on basis of the very limited evidence. The distribution of rates of return appearspositively skewed. Our best guess of ex ante risk in university education is a coefficient ofvariation of about 0.3, comparable to that in a randomly selected financial portfolio with some30 stocks. Allowing for stochastic components in earnings also markedly affects expectedreturns.
Keywords: I2; J3; 330; education; return; earnings dispersion; risk; Bildungsinvestition; Bildungsertrag; Risiko